Governance, legitimacy, and stakeholder balance: lessons from Fairtrade International. Issue 3 (7th November 2016) - Bennett, Elizabeth A.
Abstract : Purpose: This paper aims to explain why Fairtrade International (FI), an organization committed to empowering the producers of Fairtrade certified products, at times (paradoxically), excluded them from its highest bodies of governance. A within-case study of Fairtrade's inclusive and exclusive reforms over 25 years, along with insights from the social enterprise, hybrid governance and political sociology literatures, is used to generate several propositions about how voluntary sustainability standards-setting organizations (VSSSOs) engage stakeholders – especially producers – in governance. Design/methodology/approach: This study uses process-tracing methodology, which focuses on the sequential, intervening processes that link potentially important variables within a single case. It draws on data from over 100 interviews and nearly 6, 000 archival documents collected from FI and its member Max Havelaar Netherlands. Causal process observations were extracted from the documents and compiled to create a 68, 000-word chronological narrative used to evaluate six potential explanations of Fairtrade's governance reforms: legitimacy, resources, identity, oligarchic tendency, leadership and producer mobilization. Findings: This study finds that Fairtrade's inclusion/exclusion of producers reflected its desire to increase its moral legitimacy among external actors and understanding of how to signal legitimacy. The discussion proposes that VSSSOs, especially in times of heightened competition, leverage their comparative advantages to differentiate themselves from other organizations. In cases (like FI) in which the advantage is legitimacy, changing notions of legitimacy may have a destabilizing effect on governance. Originality/value: This evidence-based account of FI's governance decisions should help resolve some debates about the nature of FI's relationship with producer groups. The broader propositions offer guidance for future cross-case research aiming to explain VSSSOs' governance structure and hybrid governance, more generally. Because FI includes producers in governance to a much greater extent than most VSSSOs, it is an important case.